Reiki for promotion of health and sleep quality in hospital nursing professionals - Josane Rosenilda da Costa; Sonia Silva Marcon; Rosane Gonçalves Nitschke; Fátima Helena do Espírito Santo; Diéssica Roggia Piexak; Stefanie Griebeler Oliveira; Herbert Leopoldo de Freitas Goes; Pablo Jesús Lopez Soto (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to know the repercussions of a Reiki therapy intervention on the sleep quality of nursing professionals working in a general hospital. Methods: a qualitative-quantitative study conducted with 16 professionals from the nursing team of a hospital in northwest Paraná, who participated in an intervention consisting of six weekly Reiki sessions. Data collected from September, 2019 to March, 2020 through semi-structured interviews and application of the Pittsburgh Sleep Quality Index before and after the intervention. Results: better sleep quality, characterized by a reduction in the time to fall asleep and in nightmares, and an increase in sleeping hours. Conclusions: reiki intervention had a positive impact on the sleep quality of participants.